THE NEXUS OF SOCIO-ECONOMIC AND POLITICAL VULNERABILITY AND NON-STATISTS ACTORS CRIMINAL ACTIVITIES IN KENYA - William Oluoch, Ligawa,; Elijah Onyango Standslause, Odhiambo (IJRDO - Journal of Social Science and Humanities Research, 2016)
There are inreased criminal acts by various militia groups challenging the stability of the Kenyan government. There has been significant growth of these militia groups in the recent past which has engendered a lot of insecurity to the state. Such destructive conflicts in the transnational era need deep understanding of their genesis so that they can be managed effectively. However, this has not been the case. The government has been unable to address insecurity issues stemming from these militants. Attacks on vulnerable population are still rampant. Citizens die as a result of these activities as well as causation ofwanton destruction of property. The approach of this paper is diagnostic and prescriptive, attempting to tackle the failures of the government that has spiraled the development of these outlawed groups. With many dynamics at play such as poor governance, weak state systems and lack of political will, there is general feeling of resentments amongst the ethnic communities who feel marginalized in the post-independent era. Injustices meted against them during and in the post-colonial period have not been corrected neither have they been compensated. This discontentment breeds anger and hatred which are some of the push factors. Such indignation manifests itself through brutal and barbaric acts of these violent groups. This article addresses the ideological root causes of these terror groups. It further recommends solutions to the root causes thus providing longlasting rejoinder to the insecurity menace that bedevils the government.